Analysis of The Effect of Price Determination on Hotel Revenue (Hotel Case in Puncak, Bogor) - Swantari, Anita; Gantina, Devita; Festivalia, Filma (Jurnal Penelitian Pariwisata, 2019)
The purpose of this study is to find out the percentage of room occupancy and the room rates correlated with the benefits gained by the hotel in Puncak Bogor in the period of 2016 – 2018. This research includes the type of Descriptive and Explanatory Research of variables of prices, occupancies and incomes received by the hotel. It can be seen that the influence of price determination as measured by the room occupancy rates to the amount of hotel revenue is shown by the regression coefficient test, so, it can be stated that the occupancy rate or the number of visitors staying overnight has a very significant influence on the increase of hotel revenues.